INNOVATION IN POST-PANDEMIC E-COMMERCE - Yogi Nurfauzi; Iyad Abdallah Al-Shreifeen (CV. Adiba Aisha Amira, 2025)
The COVID-19 pandemic has been a major catalyst for the acceleration of digital technology adoption in the trade sector, particularly e-commerce. This research aims to examine the main innovations that have developed in post-pandemic e-commerce and their impact on businesses and consumers through a literature review method. The results show that innovations such as digital payment integration, artificial intelligence-based personalisation, logistics optimisation, social commerce, and cross-platform collaboration such as GoTo, have improved business operational efficiency, expanded market access, and created a more convenient and secure shopping experience for consumers. In addition, these innovations also encourage the growth of MSMEs and strengthen the digital ecosystem in Indonesia. However, challenges such as intensified competition, data security issues, and the digital divide still need to be anticipated for e-commerce growth to be sustainable in the post-pandemic era.